Oszukiwanie w przestrzeni akademickiej. O sukcesie „przedsiębiorstw” sprzedających prace dyplomowe i porażce świata akademickiego - Hejwosz-Gromkowska, Daria (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The young generation is being taught to avoid a failure in the success-oriented society. Social acceleration and consumer society created the need of instant gratification. Success is no longer perceived as a slow climbing on the social ladder rather as a car racing. The meritocratic idea assumes that the success depends on individual abilities. In the western societies there is a belief that the university diploma is necessary on the contemporary, highly competitive job market. The individual who wants to graduate from the university is required to sacrifice time, to be hard working, patient and persistent. These features have barely anything in common with the consumer society which promises the instant gratification. Thus those who are less persistent or less gifted are seeking for different solutions. Cheating may be regarded as a one of them. The aim of the paper is to analyse the offer of the selected ghostwriting companies and to explain how do they rationalize cheating in the academia.
Keywords: nieuczciwe zachowania w świecie akademickim; pisarze widma; społeczeństwo konsumpcyjne; sprzedaż prac dyplomowych